Monitoring of Performance of Russian Higher Education Organizations: Panel Data, 2015-2023 - Guba, Katerina S.; Kuchakov, Ruslan K. (Voprosy obrazovaniâ, 2025)
The purpose of this article is to present data from the Monitoring of Performance of Russian Higher Education Organizations, making it widely accessible. Since 2013, this monitoring has provided extensive information on most Russian universities and their branches, which holds great potential for addressing both university management and research problems. A review of existing studies reveals that monitoring data has already been employed to explore a wide range of issues, from factors influencing the efficiency of Russian universities to the construction of various university typologies. However, such research has been limited to a few research teams. By making panel data available in a format suitable for quantitative analysis, we can expect to broaden the reach of higher education researchers. Monitoring data for all universities and branches from 2015 to 2023 have been prepared for open access, forming an observation panel that describes 2,297 organizations, including 1,333 branches.